The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1021/ja039237w
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent and Circular Dichroic Detection of Monosaccharides by Molecular Sensors:  Bis[(Pyrrolyl)ethynyl]naphthyridine and Bis[(Indolyl)ethynyl]naphthyridine

Abstract: The push-pull conjugated molecules 2,7-bis-(1H-pyrrol-2-yl)ethynyl-1,8-naphthyridine (BPN) and 2,7-bis(1H-indol-2-yl)ethynyl-1,8-naphthyridine (BIN) adopting daad relays of proton donors (d) and acceptors (a) form multiple hydrogen-bonding complexes with various monosaccharides that possess complementary adda sequences. Although the free BPN emits blue light at lambda(max) = 475 nm in CH(2)Cl(2), its complexation with octyl beta-d-glucopyranoside gives green fluorescence at lambda(max) = 535 nm. The excellent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(36 citation statements)
references
References 41 publications
(30 reference statements)
0
35
0
1
Order By: Relevance
“…1821 Addition of simple synthetic handles to the arenes in these systems has allowed for substitution of chiral functional groups, yielding macrocycles capable of saccharide complexation as well as asymmetric catalysis and chiral recognition. 22,23 Of all of the benefits of using an arylethynyl foundation on which to build a receptor, the rigidity, and hence preorganization, they lend to the structure is particularly important. Furthermore, in the case of acyclic receptors, the axial rotation around the linear substituted alkynyl bonds provides receptors that are also conformationally flexible.…”
Section: Introductionmentioning
confidence: 99%
“…1821 Addition of simple synthetic handles to the arenes in these systems has allowed for substitution of chiral functional groups, yielding macrocycles capable of saccharide complexation as well as asymmetric catalysis and chiral recognition. 22,23 Of all of the benefits of using an arylethynyl foundation on which to build a receptor, the rigidity, and hence preorganization, they lend to the structure is particularly important. Furthermore, in the case of acyclic receptors, the axial rotation around the linear substituted alkynyl bonds provides receptors that are also conformationally flexible.…”
Section: Introductionmentioning
confidence: 99%
“…[36] In this work, our strategy entails the esterification of oligo(arylene-ethynylene)s with the N-hydroxysuccinimidyl group, which reacts with lysine moieties in proteins and enables the covalent attachment of fluorophores to biomolecules. We have demonstrated that the high quantum efficiencies, large Stokes shifts (maximum 11530 cm -1 ) and strong solvatochromism (except H-and Fsubstituted derivatives) of the oligo(arylene-ethynylene)s can confer rich photophysical characteristics upon the resultant bioconjugates.…”
Section: Discussionmentioning
confidence: 99%
“…3). Measurement of fluorescence intensity ½I 0 F =ðI F 2I 0 F Þ as a function of the inverse of Na þ concentration fit a linear relationship, indicating a 1:1 stoichiometry for the 4 · Na þ complex [20,21].…”
Section: Complexation Studies Of 4 and 5 Towards Alkali Metal Ionsmentioning
confidence: 99%